Predictors of Recurrent Ingestion of Gastrointestinal Foreign Bodies - Ian C Grimes; Bret J Spier; Lisa R Swize; Mary J Lindstrom; Patrick R Pfau (Canadian Journal of Gastroenterology)
BACKGROUND: Gastrointestinal foreign bodies are commonly encountered; however, little knowledge exists as to the causes of foreign body ingestions and why they occur repeatedly in some patients.